Identification of SERPINA1 promoting better prognosis in papillary thyroid carcinoma along with Hashimoto’s thyroiditis through WGCNA analysis - Zhang, Yihan; Xie, Xin; Zhou, Hong; Li, Bingxin; Ding, Li; Cai, Zhaogen; Song, Huaidong; Zhao, Shuangxia; Xu, Huanbai (Frontiers in Endocrinology, 2023)
Background: Hashimoto thyroiditis (HT) is an autoimmune thyroid disease. Papillary thyroid carcinoma (PTC) is the most common endocrine cancer. Coexistence rate between PTC and HT has increased recently. However, the relationship between them has still remain controversial. Method: Co-expression network was constructed by weighted gene co-expression network analysis (WGCNA) R package and identify the module of PTC associated with HT (PTC-W) from GSE138198. Protein-protein interaction network (PPI) was used to screen the hub genes. Immunohistochemical was applied to validate the expression of hub genes in tissues. Clinical data from TCGA datasets were used to analyze the prognosis of hub genes. GSEA was used to screen potential pathways of PTC associated with HT. Result: MEbrown module resents the most significance module, with 958 DEGs, were screened out in PTC-W based on WGCNA analysis. Through PPI, two genes were identified as hub genes, which were SERPINA1, FAM20A. Immunostaining validate SERPINA1 were highly expressed in PTC-W. What’s more, PTC-W group of SERPINA1 has better prognosis than PTC associated without HT (PTC-WO) group. Conclusion: Our study identified SERPINA1 promote the occurrence of PTC-W, its prognosis better than PTC-WO group. SERPINA1 promote the better prognosis of PTC-W may through tumor inhibition signaling pathway. Key words: Hashimoto’s thyroiditis (HT), papillary thyroid carcinoma (PTC), weighted gene co-expression network analysis (WGCNA), SERPINA1(Serpin Family A Member 1), gene set enrichment analysis (GSEA)